The analysis of a sudden death caused by the unusual shape of the foramen magnum stenosis - Vuković Miloš; Vuković Jelena; Maletin Miloš; Vuković Radenko (Vojnosanitetski Pregled)
Introduction. The anomalies of the size and shape of the foramen magnum (FM), followed by its stenosis, take a special place in clinical and forensic practice. The clinical picture of FM stenosis is variable, but it is not specific, which is why these anomalies are sometimes not recognized in time and are only detected by autopsy. Case report. This paper analyzes the case of a sudden death caused by the unusual shape of the FM stenosis. On autopsy, we found exostoses on the front and rear edges of the FM with their prominence into the FM. The exostoses reduced the sagittal diameter of the FM and practically divided it into two asymmetric semicircles, which is why we called this stenosis the "keyhole" stenosis of the FM. This form of the FM stenosis pushes the medulla oblongata aside, resulting in its incarceration into one of the FM semicircles. Conclusion. A stenosis of the FM can represent a threat to life, especially when combined with its unusual shape, as in our case. In this way, the critical stenosis of the FM becomes clinically clearly manifested, and there is a loss of consciousness that can also end with a sudden death, as in our case.